García Arias, Xosé Lluis (2017). Diccionariu Etimolóxicu de la Llingua Asturiana (DELLA) (A-B). Universidá d’Uviéu & Academia de la Llingua Asturiana. - Fernández Fernández, Xurde (Añada: revista d'estudios llioneses, 2020)
Recensión